Retinal Detachment in Dengue Fever – A Case Report: Doi: 10.36351/pjo.v38i4.1390 - Zaman, Saliha; Eileen Samuel; Qasim Lateef Chaudhry (Pakistan Journal of Ophthalmology, 2022)
A 20 years old female came to our hospital with sudden painless loss of vision in her right eye for two days. She was diagnosed with dengue fever two and a half weeks back and was managed conservatively. Ocular examination showed mid-dilated pupils with sub-conjunctival hemorrhage, lens opacity, vitreous hemorrhage and haze, sub-retinal hemorrhage and retinal detachment. Visual acuity in right eye was perception of light only. Ultrasound revealed moderate number of low to moderately reflective vitreous echoes and a highly reflective membrane attached to the disc suggesting retinal detachment. An urgent ophthalmologist opinion was sought followed by pars plana vitrectomy with silicon oil. She was lost to follow up after surgery.